How Will India’s One Nation One Subscription (ONOS) Policy Shape the Future of Small Indian Journal Publishers? A Perspective on Challenges - Bagga, Teena; Sawhney, Deepak; Gilani, Priyanka (Prabandhan: Indian Journal of Management, 2025)
Purpose : The proposed “One Nation One Subscription” (ONOS) policy (https://www.onos.gov.in/) in India could be a game-changer in the way our country accesses online academic journals. Currently, with 30 publishers on board, the initiative is expected to provide a vast collection of scholarly content through government-negotiated agreements, aiming to close the knowledge gap and make high-quality research more accessible to 18 million researchers and academicians. At the same time, the policy raises significant concerns about its impact on Indian publishers, particularly with regard to sustainability, revenue models, and competition within the publishing ecosystem. Methodology : This paper adopted a qualitative approach to examine the ONOS policy, focusing on insights from a top publisher of management journals to explore its potential implications. Findings : The ONOS initiative is going to provide over 18 million students, teachers, and researchers with access to scholarly e-journals, thereby filling critical knowledge gaps across the nation. However, small Indian journal publishers face significant challenges, including financial pressures and threats to content diversity. For ONOS to succeed, it must balance broad accessibility with the long-term sustainability of India’s journal publishing industry. Practical Implications : ONOS will be of immense help to improve access to academic resources for further development of education and research in the country. Nonetheless, its true impact—particularly on the survival of smaller Indian journal publishers—will become evident as the journal publishing landscape continues to evolve in the coming years.